The Definition of Success in Education and New Approaches - Gezer, Ülkü (Edp Sciences, 2017)
Do postmodern approaches replace the modern approaches while the classical approach is replaced by modern approaches in education? It seems that the changing needs of the societies lead to the creation of new paradigms. Our paradigms which derived from preexisting knowledge, experiences, and implied conditioning, constitute our 'way to perceive a situation' and manage our perspective which directs our behaviors. Thus, globalization, accelerating the flow of information through the internet network, should change the way we observe a situation and our perspective on education and educators. As a continuation of this, our point of view should change our behavior. Success is a combination of many factors mentioned above, which are related to each other. Hence, the study intends to examine the utmost prominent factors in the education systems that may be taken as an example and after comparing these factors with Turkey's status, the study intends to investigate which lessons could be taken from this knowledge.
Keywords: Visual Arts Education; Teacher; New